Effectiveness of STCW Standards in Navigating Digital Transformation Challenges in the Shipping Sector - Disca Panji Trianggit; Larsen Barasa; Bambang Sumali (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The effectiveness of the global International Convention on Standards of Training, Certification and Watchkeeping (STCW) framework remains critically uncertain amidst the rapid digital transformation (AI, IoT) in the maritime industry. This study utilized a rigorous qualitative approach involving Cross-Group Comparisons among Maritime Education and Training (MET) Lecturers, Shipping Company Experts, and Experienced Seafarers (N=30) via semi-structured interviews. The findings show that the overall effectiveness is Very Good, largely attributed to proactive, company-specific training that successfully bridges immediate gaps in e-navigation and digital logbook proficiency. However, a significant Simulator-Reality Dissonance was found regarding troubleshooting Automated Ship Systems, and Regulatory Lag was confirmed in integrating practical Cybersecurity competence (rated Moderate). The research concludes that economic motivation drives localized competence, yet this fragmentation poses risks to operational consistency and increases administrative burden, challenging social sustainability. Recommendations urge the formalization of successful local Standard Operating Procedures (SOPs) into the STCW Code and targeted investment in diagnostic simulation training.